Effect of duodenal glucose and acute hyperglycemia on rectal perception and compliance in response to tension-controlled rectal distension in healthy humans - Hernando-Harder, Ana C.; Singer, Manfred V.; Harder, Hermann (Digestive diseases and sciences, 2008)
Background Acute changes in blood glucose concentration affect gastrointestinal motor and sensory function. Tone and distensibility contribute to intact rectal function. Aims To test the effects of duodenal glucose (euglycemic hyperinsulinemia), intravenous glucose (hyperglycemic hyperinsulinemia), and saline (euglycemic normoinsulinemia as control) on rectal perception and compliance in response to tension-controlled rectal distension. Methods During duodenal glucose at 2 kcal min−1, marked hyperglycemic clamp (∼13 mmol L−1), or saline as control, responses to fixed-tension rectal distension, applied by means of a computerized tensostat, were compared randomized on three separate days in eight healthy subjects. Results At discomfort level (score 3 on the 0-4 rectal score scale), perception of rectal distension was significantly higher during euglycemic hyperinsulinemia (45 ± 3 g cm−2 tolerance) and significantly lower during hyperglycemia (83 ± 4 g cm−2 tolerance), both reaching significance versus control (64 ± 6 g cm−2 tolerance; P < 0.05). At this level, no relevant variations of rectal compliance were seen, which were 10.3 ± 1 mL mmHg−1 during duodenal glucose, 9.5 ± 1 mL mmHg−1 for the group with hyperglycemia, and 9.7 ± 2 mL mmHg−1 for the control. Conclusion Duodenal glucose provokes rectal hypersensitivity whereas acute hyperglycemia contributes to rectal hyposensitivity. Despite different rectal tensosensitivity, rectal compliance remains virtually unchanged. Any dysfunction may cause rectal complaints.